EXTH-60. ONCR-GBM, A NOVEL ARMED ONCOLYTIC HSV-1 VECTOR ENGINEERED FOR EFFICACY AND SAFETY IN GLIOBLASTOMA. (14th November 2022) - Strathdee, Craig; Giovannoni, Federico; Molgora, Martina; Kong, Lingxin; Floyd, Michael; Teng, Jian; Gyulakian, Yulia; Grzesik, Peter; Farkaly, Terry; Denslow, Agnieszka; Feau, Sonia; Jacques, Judith; et al.
Abstract: Glioblastoma (GBM) is the most common type of primary brain tumor in adults, with a 5-year overall survival of only 7%. Oncolytic viruses are a promising and active area of research in GBM with the recent approval of an oncolytic HSV-1 vector, teserpaturev (Delytact, also known as G47Δ, Daiichi Sankyo) for recurrent GBM based on an overall survival of 92% at 1 year. G207, an HSV-1 vector more attenuated than teserpaturev, recently reported acceptable tolerability with evidence of responses in children with recurrent or progressive high-grade glioma. These vectors are not expressing any cDNA transgene that may enhance and prolong antitumor activity. We report here the development of ONCR-GBM, an oncolytic HSV-1 vector specifically engineered for safety using a microRNA attenuation strategy to limit viral replication in healthy cell type of the CNS. ONCR-GBM has been developed from a novel potently oncolytic strain of HSV-1 and optimized for infection of GBM tumor cells. Antitumor efficacy has been further enhanced through the expression of multiple payloads designed to modify the immunosuppressive tumor microenvironment of GBM. We previously reported that a vector expressing IL-12 and a PD-1 antagonist nanobody achieved > 90% survival after a single injection in the GL261-Nectin1 orthotopic model. This vector promoted immune cell recruitment and activation in tumors and protected surviving animals from a subsequent tumor rechallenge. Additional payloads selected for interfering with the immune suppressive stroma in GBM have been evaluated for potentiating the response of IL-12 and anti PD-1 expressing HSV-1. We will present the outcome of the in vivo screen, and the selection of the optimal combination of payloads featured in ONCR-GBM clinical candidate.